Hemoglobin During and Following a 4-Week Commercial Saturation Dive to 200 m - Łuczyński, Damian; Lautridou, Jacky; Hjelde, Astrid; Monnoyer, Roxane; Eftedal, Ingrid (Frontiers in Physiology, 2019)
Commercial saturation divers must acclimatize to hyperbaric hyperoxia in their work environment, and subsequently readjust to breathing normal air when their period in saturation is over. In this study we measured hemoglobin (Hb) during and following four weeks of heliox saturation diving in order to monitor anemia development and the time for Hb to recover post-saturation. Male commercial saturation divers reported their capillary blood Hb daily, before and during 28 days of heliox saturation to a working depth of circa 200 m (n=11), and for 12 days at surface post-saturation (n=9-7), using HemoCue 201+ Hb devices. Hb remained in normal range during the bottom phase, but fell during the decompression; reaching levels of mild anemia (≤ 13.6 g/dL) the day after the divers' return to the surface. Hb was significantly lower than the pre-saturation baseline (14.7 ± 1.1 g/dL) on the fifth day post-saturation (12.8 ± 1.8 g/dL, P= 0.028), before reverting to normal after six-seven days. At the end of the 12-day post-saturation period, Hb was not statistically different from the pre-saturation baseline. In conclusion, the development of mild anemia during decompression supports the transient fatigue that commercial saturation divers experience post-saturation.